Modelagem molecular de inibidores da enzima tirosinase - MARTINS, Lucas de Sousa (Universidade Federal do Pará, 2022)
The enzyme Tyrosinase (TYR), responsible for the catalysis of the early stages of melanogenesis in various organisms, is described in some groups. Among those that stand out: hyperpigmentation, melasma and skin cancer, in not melanoma forms and malignant melanoma. In general, dysfunctions are treated with depigmenting agents, TYR enzyme alerts. However, among them is the kojic acid (KA), marked side effects. Such phenomena make a TYR a model of biological development of drug prototypes. In the meantime, I investigated some TYR enzyme inhibitory genes, in particular AK and analogous plants, as well as a Tropolone and some benzaldehyde derivatives, structurally related to the natural substrates of TYR (L-Tyrosine and L-Dopa), as the Molecular Docking, Molecular Dynamics (MD), and the Linear Interaction Energy (LIE) method, used to calculate the free binding energy of the systems. Specifically application of Molecular Docking defined the mode of binding of the inhibitors in the TYR site, being possible to quantify how interactions occur in the systems. As the MD simulations, they exhibited the effect of the enzyme with different inhibitors and how they act when complexed with a TYR enzyme, using a copper dummy atom model. Thus, the results obtained by LIE were concordant with the experimental results, obtaining an R2 of 0.91 in a linear regression of LIE vs Experimental, and this allowed to analyze how Tropolona, KA, MOL2 and MOL3 interactions with the important to the active site of TYR. Thus, the results achieved at work contributed significantly to the achievement of inhibition of the TYR enzyme, helping to combat the evils caused by a cycle of melanin production in organisms.